Common endpoints for non-commutative suzuki mappings - Thanomsak Laokul (2020)
© 2019 by the Mathematical Association of Thailand. In this paper, we prove an endpoint theorem for multi-valued Suzuki mappings in uniformly convex hyperbolic spaces. As a consequence, we obtain a common endpoint theorem for a pair of single-valued and multi-valued Suzuki mappings without the commutative condition. Our results extend and improve the results of Espinola et al. (2015), Saejung (2016), Kudtha and Panyanak (2018) and many others.